2016
DOI: 10.1021/acs.est.5b06007
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hydrophilic and Hydrophobic Sites on Polypropylene Nonwoven for Oil Spill Cleanup: Two Dilemmas Affecting Oil Sorption

Abstract: This article mainly deals with the following dilemmas, which affect oil sorption and sorbent preparation: (1) hydrophobization could facilitate oil sorption but has adverse impacts on emulsion sorption; (2) micropores of conventional oil sorbent do not exhibit effective emulsion sorption. To solve the above contradictions, hydrophilic and hydrophobic sites were fabricated onto polypropylene (PP) nonwoven through electron beam radiation and subsequent ring-opening reaction. Further, a similar structure without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
(29 reference statements)
0
38
0
Order By: Relevance
“…The initial increase is maybe due to the availability of free radicals generated for grafting reaction. When the initiator concentration rises above a certain value, increased free radical concentration results in a homopolymerization which diminishes the graft copolymerization [23,47]. This result can be attributed to the fact that free radical generation process will increase with increasing levels of AIBN, which enhances the grafting degrees.…”
Section: Effect Of the Initiator Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial increase is maybe due to the availability of free radicals generated for grafting reaction. When the initiator concentration rises above a certain value, increased free radical concentration results in a homopolymerization which diminishes the graft copolymerization [23,47]. This result can be attributed to the fact that free radical generation process will increase with increasing levels of AIBN, which enhances the grafting degrees.…”
Section: Effect Of the Initiator Concentrationmentioning
confidence: 99%
“…However, it still remains challenges to water-oil separation, eco-friendly ways of oil removing, free-floating oil skimmers as well as environmental concerns. In order to improve the oil sorption performance of virgin PP fiber, many modifications have been studied but graft polymerization is one the most effective methods to ameliorate its chemical properties and sorbent surface [22,23]. Some monomer such as butyl acrylate [19,[24][25][26], lauryl methacrylate [27,28] have been successfully grafted.…”
Section: Introductionmentioning
confidence: 99%
“…Among existing technologies, absorption by oil sorbent materials is considered to be one of the more economical and effective way of cleaning up floating oil from contaminated waters . Compared with the most common synthetic oil sorbent materials such as polypropylene fiber, polydimethylsiloxane sponge, and electrospun fiber, natural organic fibers (e.g., protein fiber and plant fiber) have increasingly attracted attention as oil sorbents because of their low cost, acceptable oil sorption performance, and biodegradability …”
Section: Introductionmentioning
confidence: 99%
“…The adsorption method is attractive due to its sorption efficiency and the possibility for collecting and reuse the adsorbed products. In this context, several studies have shown the removal of oil from water using adsorbent materials, such as sugarcane bagasse, vegetables fibers, raw cotton, poly(tetrahydrofuran), polypropylene, and polyurethane foams …”
Section: Introductionmentioning
confidence: 99%